(untitled) (Research, Society and Development, 2021)
Studies on rainfall distribution favor the planning of the amount of water necessary for the development of human activities, whether personal, industrial or agricultural. The objective is to statistically model the monthly mean precipitation values ​​and estimate the respective precipitations at different levels of probability, through the gamma distribution, for Barbalha - Ceará, in the period 1973 to 2017. The Gamma probabilistic function model and the adherence test Monthly data were evaluated by the Kolmogorov-Smirnov test. Means range from 3.6 mm (August) to 237.4 mm (March). The four-month period with the highest rainfall is registered between January and April, and the one with the lowest indices occurs between June and September. The oscillation of the alpha parameter occurred from 0.829 (August/September) to 0.896 (March), the beta parameter oscillated between 0.851 (August/September) to 0.922 (March). Regarding the empirical probability for occurrences of total annual rainfall, the percentage stands out 50% and 70% with rain possibilities higher than the historical average.